Effects of aging-related muscle degeneration on dynamic stability during walking: a musculoskeletal computer simulation study - Kudo, Shoma; Fujimoto, Masahiro; Nagano, Akinori (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAging-related deficits in the physiological properties of skeletal muscles limit the control of dynamic stability during walking. However, the specific causal relationships between these factors remain unclear. This study evaluated the effects of aging-related deficits in muscle properties on dynamic stability during walking.MethodsWalking movements were simulated using two-dimensional musculoskeletal models consisting of 18 Hill-type muscles. To assess the effects of aging-related deficits in muscle function on dynamic stability during walking, five models with different muscle properties were created, namely young adult (YA) and older adult (OA) models, models with reduced maximum isometric muscle force, reduced maximum muscle contraction velocity, and prolonged muscle deactivation time (∆F, ∆V, and ∆T models, respectively). The margin of stability (MoS) was used as a measure of dynamic stability during walking.Results and DiscussionThe MoS value of the OA model was greater than that of the YA model, and the ∆F model yielded a larger MoS value than those of the ∆V and ∆T models. Therefore, the OA model achieved a more dynamically stable state than the YA model and the ∆F model required a more stable state to sustain continuous walking compared to the ∆V and ∆T models. These findings indicate that aging-related deficits in muscle function limit the control of dynamic stability during walking with the degeneration of maximum isometric muscle force being the most influential factor. These findings could aid in the development of an intervention program to reduce the risk of falls in older adults effectively.